Far Cortical Locking Technology for Fixation of Periprosthetic Distal Femur Fractures: A Surgical Technique - Ries, Zachary G.; Marsh, J. L. (The Journal of Knee Surgery, 2013)
Far cortical locking screws have been shown to form greater amounts of callus in ovine studies when compared to traditional locking plates. These screws have recently become available for clinical use. This article describes the indications and surgical technique for far cortical locking screws, with a focus on distal femur periprosthetic fractures.
Keywords: periprosthetic fracture; distal femur fracture; far cortical locking